Electrical and photoelectric properties of MoN/p-CdTe and MoN/n-CdTe heterojunctions - Taras Kovaliuk; Mykhaylo Solovan; Pavlo Maryanchuk (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
Due to the physical properties of MoN and ITO thin films, it was decided to create MoN/p-CdTe and MoN/n-CdTe heterostructures and investigate their electrical and photoelectric properties. The method of reactive magnetron sputtering was used to create thin MoN and ITO films on single crystal CdTe substrates with different conductivity types. To manufacture test heterostructures, the following CdTe crystal substrates were used: 1) p-type conductivity, grown by Bridgman technique at low cadmium vapor pressures; 2) n-type conductivity, grown by Bridgman technique at high cadmium vapor pressures. During the deposition process, the argon pressure in the vacuum chamber was 0.4 Pa. The power of the magnetron was 30 W, the sputtering process continued 5 min at a substrate temperature of 150°C. I-V characteristics of the heterostructures at different temperatures were measured, the height of the potential barrier, the values of the series and shunt resistance were determined. Electrical and photoelectric properties of the heterostructures were studied, and the dominant mechanisms of current transfer at forward displacements was established. The tunnel-recombination mechanism was found to be the dominant mechanism of current transfer in the MoN/p-CdTe and MoN/n-CdTe heterostructures. It was shown that the photoelectric parameters for the MoN/p-CdTe heterostructure are higher than those for MoN/n-CdTe. MoN/p-CdTe heterojunctions have the following photoelectric parameters: open-circuit voltage Voc = 0.4 V, short-circuit current Isc = 24.6 mA/cm2 at an illumination intensity of 80 mW/cm2. This makes them a promising material for the manufacture of detectors of various radiation types.